Burrowing behaviour of rats: Strain differences and applicability as well-being parameter after intracranial surgery. (August 2022) - Riedesel, Ann-Kristin; Bach-Hagemann, Annika; Abdulbaki, Arif; Talbot, Steven R; Tolba, René; Schwabe, Kerstin; Lindauer, Ute
In mice, burrowing is considered a species-typical parameter for assessing well-being, while this is less clear in rats. This exploratory study evaluated burrowing behaviour in three rat strains during training and in the direct postoperative phase after complex intracranial surgery in different neuroscience rat models established at Hannover Medical School or Aachen University Hospital. Male Crl:CD (SD; n  = 18), BDIX/UlmHanZtm (BDIX; n  = 8) and RjHan:WI (Wistar; n  = 35) rats were individually trained to burrow gravel out of a tube on four consecutive days. Thereafter, BDIX rats were subjected to intracranial injection of BT4Ca cells and tumour resection (rat glioma model), SD rats to injection of 6-hydroxydopamine (6-OHDA) or vehicle (rat Parkinson's disease model) and Wistar rats to endovascular perforation or sham surgery (rat subarachnoid haemorrhage (SAH) model). Burrowing was retested on the day after surgery. During training, BDIX rats burrowed large amounts (mean of 2370 g on the fourth day), while SD and Wistar rats burrowed less gravel (means of 846 and 520 g, respectively). Burrowing increased significantly during training only in Wistar rats. Complex surgery, that is, tumour resection (BDIX), 6-OHDA injection (SD) and endovascular perforation or sham surgery for SAH (Wistar) significantly reduced burrowing and body weight, while simple stereotactic injection of tumour cells or vehicle did not affect burrowing. Despite the training, burrowing differed between the strains. In the direct postoperative phase, burrowing was reduced after complex surgery, indicating reduced well-being. Reduced burrowing was accompanied with postoperative weight loss, a validated and recognised quantitative measure for severity assessment.